(untitled) (Interdisciplinary Research in Education, 2022)
A desk review was done to analyze the relevance of Vipassana with the overall dimensions of health and to find out its interconnection with the school curriculum for enhancing the education sector and shifting the paradigm. Secondary data were collected via an internet online portal and analyzed by making a theme. Literature shows that Vipassana has a tremendous positive impact on human health dimensions like physical, mental, social, psychological, and spiritual health. Vipassana with its moral code and precepts is found to help in fostering peaceful feelings, equanimity, and compassion, thus assisting social integrity. Relying on this fact, there is a great possibility of interconnecting Vipassana with the school curriculum. No review has been found on social well-being and spiritual health in a collaborative form which could be a future recommendation.